2015
DOI: 10.1038/nmat4456
|View full text |Cite
|
Sign up to set email alerts
|

Observation of superconductivity induced by a point contact on 3D Dirac semimetal Cd3As2 crystals

Abstract: Three-dimensional (3D) Dirac semimetals, which possess 3D linear dispersion in the electronic structure as a bulk analogue of graphene, have lately generated widespread interest in both materials science and condensed matter physics. Recently, crystalline Cd3As2 has been proposed and proved to be a 3D Dirac semimetal that can survive in the atmosphere. Here, by using point contact spectroscopy measurements, we observe exotic superconductivity around the point contact region on the surface of Cd3As2 crystals. T… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
171
0
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 239 publications
(183 citation statements)
references
References 37 publications
8
171
0
4
Order By: Relevance
“…Interestingly, we also notice two recent point contact studies on Cd 3 As 2 polycrystal and single crystal, respectively. 43,44 In both studies, indication of superconductivity was found around the point contact region on the surface, with T c comparable to ours. In particular, no superconductivity is observed by the 'soft' point contact technique, therefore it was suggested that the superconductivity observed around the point contact region under the 'hard' tip might be induced by the local pressure.…”
Section: Pressure-induced Superconductivitysupporting
confidence: 86%
See 3 more Smart Citations
“…Interestingly, we also notice two recent point contact studies on Cd 3 As 2 polycrystal and single crystal, respectively. 43,44 In both studies, indication of superconductivity was found around the point contact region on the surface, with T c comparable to ours. In particular, no superconductivity is observed by the 'soft' point contact technique, therefore it was suggested that the superconductivity observed around the point contact region under the 'hard' tip might be induced by the local pressure.…”
Section: Pressure-induced Superconductivitysupporting
confidence: 86%
“…In particular, no superconductivity is observed by the 'soft' point contact technique, therefore it was suggested that the superconductivity observed around the point contact region under the 'hard' tip might be induced by the local pressure. 44 In this sense, our bulk resistance measurements under hydrostatic pressure confirm pressure-induced superconductivity in Cd 3 As 2 , although the local pressure under the 'hard' tip is more like uniaxial stress.…”
Section: Pressure-induced Superconductivitysupporting
confidence: 55%
See 2 more Smart Citations
“…We notice that this kind of setup has recently been utilized to study the pressure-induced superconductivity in Cd 3 As 2 . 44 Furthermore, we point out that the lattice strain would generally be inhomogeneous in real strained samples, and more complicated strain profiles could be naturally realized. Given that the current technology can map out strain distribution with nanometer spatial resolution and with a precision~0.1%, 45 as long as the strain is slowly varying, one can compute the effective metric and study the quasiparticle propagation under artificial gravity using the idea presented here.…”
Section: Discussionmentioning
confidence: 97%